STACKED ELECTRIC DOUBLE-LAYER CAPACITOR USING CARBON NANOTUBES - SHIUE LIH-REN; GOTO MASAMI (2009)
PROBLEM TO BE SOLVED: To solve the following problems: it is practically impossible to drive a high-voltage load unit operating at 12 volts or higher by using an electric double-layer capacitor (EDLC) singly because of low voltage per unit cell; the system connects multiple devices in series to achieve a required voltage and further requires a protective circuit, so that its weight, size, and cost increase; and there is a difficulty in manufacturing a cylindrical electrode because a metal sheet is cured by high-temperature treatment for evaporation of a carbon nanotube (CNT) film though a binder-free EDLC (requiring no binders) which directly evaporates CNTs is ideal. SOLUTION: Carbon nanotubes (CNTs), which have high specific surface area and high conductivity, are promising as a material for an electric double-layer capacitor (EDLC) having high energy density and a low ESR value. By using a stacking method, in which CNTs are directly evaporated onto an electrode and multiple sheets are stacked, a high voltage can be achieved without using a protective circuit. Furthermore, the high operating voltage EDLC can use a portion of a metal housing or the like of a load unit as an electrode of the EDLC, and can be incorporated in the load unit. COPYRIGHT: (C)2009,JPO&INPIT